Clinical Diagnosis of the Dampness and Mold Hypersensitivity Syndrome: Review of the Literature and Suggested Diagnostic Criteria - Valtonen, Ville (Frontiers in Immunology, 2017)
A great variety of non-specific symptoms may occur in patients living or working in moisture damaged buildings. In the beginning these symptoms are usually reversible, mild and present irritation of mucosa and increased morbidity due to respiratory tract infections and asthma-like symptoms. Later, the disease may become chronic and a patient is referred to a doctor where the assessment of dampness and mold hypersensitivity syndrome (DMHS) often presents diagnostic challenges. Currently, unanimously accepted laboratory tests are not yet available. Therefore, the diagnosis of DMHS is clinical and is based on the patient´s history and careful examination. In this publication I reviewed contemporary knowledge on clinical presentations, laboratory methods and clinical assessment of DMHS. From the literature, I have not found any proposed diagnostic clinical criteria. Therefore, I propose five clinical criteria to diagnose DMHS: 1) the history of mold exposure in water-damaged buildings 2) increased morbidity to due infections 3) sick building syndrome 4) multiple chemical sensitivity 5) enhanced scent sensitivity. If all the five criteria are met, the patient has a very probable DMHS. To resolve the current problems in assigning correct DMHS diagnosis, we also need novel assays to estimate potential risks of developing DMHS.